Effect of Ecological, Economic and Social Factors on the Implementation of ISO 14001 Environmental Management System in Heavy Industries in Indonesia - Mahzun, Ridwan; Thamrin, Thamrin; Bahruddin, Bahruddin; Nofrizal, Nofrizal (International Journal of Energy Economics and Policy, 2020)
This study originally tried to examine the influence of ecological, economic and social factors on the implementation of an environmental management system by taking a case study in heavy industry from a shipyard in Batam Indonesia with reference to ISO 14001: 2015 Environmental Management System (EMS) standards. EMS is a framework that helps companies to manage the environmental impacts that arise from their activities. According to Law No. 32/2009, EMS includes policies on the arrangement, utilization, development, maintenance, recovery, supervision and control of the environment. The method used is Structural Equation Modeling (SEM), with a survey method by distributing questionnaires to respondents who know the work of the shipyard industry and the implementation of environmental management systems in this heavy industry. The study results show that economic and social factors have a positive effect on the application of ISO 14001 environmental management systems in Heavy Industries in Indonesia. These findings indicate the importance of applying ISO 14001 in heavy industry, in particular, and the importance of considering various ecological, social and economic conditions of the company in such implementation. Keywords: ecology, social factors, environmental management systems, heavy industry, Indonesia. JEL Classifications: Q57, Q56 DOI: https://doi.org/10.32479/ijeep.8984